(3cJGH GdcQeIs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s
(3ChdgG (B:s
(3bhd Mfjf Hf GSMGb ajeG PcQg LGdjfhS ai GdLRA GdQGHY ef GdebGdI GdKGfjI ef cJGHg ai bhi GdCOhjI hGdCZPjI s
(3BNQgG (B:s
(3dGSjeG EPG QTi Ydi GdebOGQ GdPi bO WHNJ Hg YfO EOQGcgG TQGH TQGH fGgjc Hg ef GdLhOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG CKGQ QWhHI TOjOIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs